2019
DOI: 10.1371/journal.pone.0214395
|View full text |Cite
|
Sign up to set email alerts
|

The unmet needs of family members of patients with progressive neurological disease in the Czech Republic

Abstract: BackgroundCaring for patients with a progressive neurological disease (PND) causes stress that may impact on the state of health as well as the quality of life of the caring family.ObjectiveThe aim of the study was to explore the unmet needs of the family members of patients with PND in advanced stages.MethodsGrounded theory (constructivist approach) was used to conceptualize the patterns of unmet care needs. Data collection methodology involved focus groups (n = 4) and interviews, in which a total of 52 peopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The discussions and interviews were recorded by a voice recorder, transcribed verbatim and anonymized to ensure confidentiality. On the basis of the initial analysis, three main themes were selected, and then analyzed individually: 1. unmet needs of patients with PND [13], 2. unmet needs of family members [14], and 3. provision of information to patients and adaptation to the disease. This article describes the analysis of domain 3 only.…”
Section: Methodsmentioning
confidence: 99%
“…The discussions and interviews were recorded by a voice recorder, transcribed verbatim and anonymized to ensure confidentiality. On the basis of the initial analysis, three main themes were selected, and then analyzed individually: 1. unmet needs of patients with PND [13], 2. unmet needs of family members [14], and 3. provision of information to patients and adaptation to the disease. This article describes the analysis of domain 3 only.…”
Section: Methodsmentioning
confidence: 99%
“…Contemporary social and economic realities were sometimes acutely in conflict with cultural patterns. The issues of caregivers’ confusions on sharing responsibilities with professional care providers, as well as their uncertainty regarding their role in care of severely ill patients, followed by burdens and loss of caregivers’ dignity were also reported by recent Norwegian, Czech and Iranian qualitative studies [ 25 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 96%
“…For example, Baji and colleagues demonstrated the impact of demographic changes in Poland and Eastern Europe, and changes to the familial system of care for the elderly and dying urge the necessity for action in EoL care [ 24 ]. The unmet needs in all constructs decreased quality of life of family members and increased the care burden [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…We observed that sadness and fear were the most clearly associated sentiments, although anger and surprise are reported in our work. Compelling evidence has claimed that the impact of neurological disorders on the relatives of affected patients is a largely underestimated issue and needs more political and public awareness [33,34]. Thus, understandably, Twitter can be an ideal platform to turn to in order to express your needs and seek social and community support.…”
Section: Discussionmentioning
confidence: 99%